2015
DOI: 10.7205/milmed-d-14-00499
|View full text |Cite
|
Sign up to set email alerts
|

Males and Females Respond Similarly to Walking With a Standardized, Heavy Load

Abstract: Females in the military sustain a higher incidence of lower extremity injuries compared to males. Previous investigations of gender differences during load carriage used loads normalized to body mass; as a result of anthropometric and strength differences between genders, this may partially normalize to strength, masking gender or size differences in response to load. We compared gait kinetics and kinematics between genders based on a standardized load, instead of loads relative to body mass. 11 males and 11 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 40 publications
4
26
0
Order By: Relevance
“…Both males and females increased PS hip and knee flexion angle as load increased 38 . Furthermore, similar increases were seen in external knee flexion and ankle dorsiflexion moments with the addition of load 37,38 . This research is limited as only sagittal plane biomechanics were reported, however it does indicate at least some level of similarity between males and females with the addition of load during walking.…”
Section: Walking With Body Borne Loadsupporting
confidence: 56%
See 1 more Smart Citation
“…Both males and females increased PS hip and knee flexion angle as load increased 38 . Furthermore, similar increases were seen in external knee flexion and ankle dorsiflexion moments with the addition of load 37,38 . This research is limited as only sagittal plane biomechanics were reported, however it does indicate at least some level of similarity between males and females with the addition of load during walking.…”
Section: Walking With Body Borne Loadsupporting
confidence: 56%
“…When serving in these infantry positions, military personnel can be required to run with very large loads which may contribute to the high rate of injury seen by females in the military 3 . To date, sex comparisons during loaded locomotion have been limited to analyzing sagittal plane biomechanics while walking with load, where no differences between males and females have been observed 37,38 . When running without load, differences in the frontal and transverse planes, but not the sagittal plane, have been observed between males and females 39,40 , yet little to no research exists directly comparing sex differences when running with military relevant loads.…”
mentioning
confidence: 99%
“…While examining a standardized load of 22 kg at a predetermined marching speed, there were no lower limb kinetic or kinematic variables were significantly different between the sexes 35 . Krupenevich et al speculated that the lack of biomechanical adaptation to the addition of load may lead to higher injury rates among female trainees and soldiers; If females fail to exhibit these sex-specific differences compared to males during load carriage, it may be that they are not making the adaptations necessary to safely carry standardized loads.…”
Section: Sex Dimorphism In Load Carriage Biomechanicsmentioning
confidence: 99%
“…When males and females don body borne load relative to their weight and march at a self-determined speed, there is a lack of significant differences between the sexes in gait mechanics 35,36 . While examining a standardized load of 22 kg at a predetermined marching speed, there were no lower limb kinetic or kinematic variables were significantly different between the sexes 35 .…”
Section: Sex Dimorphism In Load Carriage Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation